Anthropogenically-induced population increases in sympatric breeding arctic geese incur apparent competition consequences - Nissley, Clark; Williams, Christopher K.; Abraham, Kenneth F.; Russo-Petrick, Kelly (Wildfowl, 2024)
Populations of Lesser Snow Geese Anser caerulescens caerulescens and Cackling Geese Branta hutchinsii have increased substantially since the mid-20th century because of their utilisation of agricultural crops as a food resource on their wintering grounds. In contrast, Atlantic Brant Geese Branta bernicla hrota, which specialise in feeding on submerged marine vegetation in winter, have not capitalised on the availability of agricultural crops to the same extent. On the breeding grounds, Atlantic Brant are also adversely affected by multiple forms of competition from other sympatrically-nesting goose species. There has however been little research on apparent competition between these three species. Apparent competition occurs whenever the presence of one species leads to a reduced population density of another species when they share a generalist predator. To determine whether apparent competition stemming from higher goose nest densities might be a functional mechanism in limiting Atlantic Brant Goose reproduction, we monitored artificial nest survival in high, medium, and low goose nest densities at East Bay, Southampton Island, Nunavut, Canada in July 2015. Eggs in artificial nests located in high-density plots had the lowest survival probabilities compared to those in medium- and low-density plots. These results support the hypothesis that the increase in nest densities resulting from anthropogenically-induced population increases of sympatric native competitors could induce decreased breeding success and a cumulative decline in numbers of nesting Atlantic Brant via apparent competition.